Narrativa de una casa porfiriana: sus representaciones simbólicas y de género - Ruiz, Emiliano (Universidad ORT Uruguay, 2017)
Social and cultural history of the house inevitably refers to the study of everyday life and its symbolic context. Studying human living spaces mean going back to the cave age, however, this time the main purpose is to briefly outline the domestic space, particularly porfiriana house and the complex web of symbolic representations that are generated between the inhabitants and within its context and their special distribution. It is unthinkable to study «the house» without placing it in its immediate surroundings, that is, the city that hosts it. An interpretative analysis of some houses, the object of study is done, to answer some questions as to the relationships of power that are exercised within them, and in many cases reflect the social, economic, moral and cultural customs the time. Cultural heritage home built allows analysis from a wide variety of positions, including gender.